Calidad de servicio y su impacto en la satisfacción del cliente en un mercado cooperativo, distrito de Chorrillos (Lima, Perú), 2022 - Cecilio Llamocca, Nely Lisett (2025)
Organizations have always aimed for excellence in service delivery. This study aimed to examine the influence of service quality on customer satisfaction in a cooperative market environment. To enhance understanding, both service quality and customer satisfaction were divided into five distinct dimensions. From a methodological standpoint, the study employed a quantitative approach with a causal correlational scope and a non-experimental design. The sample comprised 132 regular customers of the establishment under study, who completed a questionnaire containing 30 structured questions in Likert scale format. After data collection and analysis, a p-value of less than 0.05 and a Nagelkerke coefficient of 0.393 were obtained. The results demonstrated that service quality has a significant impact on customer satisfaction.